Anatomical patterns of recurrence following biochemical relapse after post‐prostatectomy salvage radiation therapy: a multi‐institutional study. (26th February 2017) - Jackson, William C.; Desai, Neil B.; Abugharib, Ahmed E.; Tumati, Vasu; Dess, Robert T.; Lee, Jae Y.; Zhao, Shuang G.; Soliman, Moaaz; Folkert, Michael; Laine, Aaron; Hannan, Raquibul; Zumsteg, Zachary S.; et al.
Abstract : Objectives: To characterise the frequency and detailed anatomical sites of failure for patients receiving post‐radical prostatectomy (RP) salvage radiation therapy (SRT). Patients and Methods: A multi‐institutional retrospective study was performed on 574 men who underwent SRT between 1986 and 2013. Anatomical recurrence patterns were classified as lymphotrophic (lymph nodes only), osteotrophic (bone only), or multifocal if both were present. Isolated first failure sites were defined as sites of initial clinically detected recurrence that remained isolated for at least 3 months. Results: The median follow‐up after SRT was 6.8 years. The 8‐year rates of local, regional, and distant failure for patients undergoing SRT were 2%, 6%, and 21%, respectively. Of the 22% men (128 of 574) who developed a clinically detectable recurrence, 17%, 50%, and 31% were lymphotrophic, osteotrophic, and multifocal, respectively. The trophic nature of metastases was prognostic for distant metastases‐free survival (DMFS) and prostate cancer‐specific survival (PCSS); the 10‐year rates of DMFS were 18%, 5%, and 7% ( P < 0.01), and PCSS were 78%, 68%, and 56% ( P < 0.01), for lymphotrophic, osteotrophic, and multifocal failure patterns, respectively. Conclusions: We demonstrate that trophism for metastatic site has significant prognostic impact on PCSS in men treated with SRT. Radiographic local failure is an uncommon event after SRT when compared to historical data of patients treated with surgery monotherapy. However, distant failure remains a challenge in this patient population and warrants further therapeutic investigation.